2020
DOI: 10.1136/bmjopen-2020-040262
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of prehabilitation prior to elective surgery compared to usual preoperative care: protocol for a systematic review of economic evaluations

Abstract: IntroductionPreoperative functional capacity is an important predictor of postoperative outcomes. Prehabilitation aims to optimise patients’ functional capacity before surgery to improve postoperative outcomes. As prolonged hospital stay and postoperative complications present an avoidable use of healthcare resources, prehabilitation might also save costs.The aim of this systematic review is to investigate the cost-effectiveness of prehabilitation programmes for patients awaiting elective surgery compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…Cost remains one of the major barriers for the adoption of new healthcare systems. This theme was considered important by experts, ‘cost effectiveness of prehabilitation programmes’, and while there are proposed models for evaluating the cost effectiveness of prehabilitation programmes, 20 , 21 current literature is lacking. Other priorities identified, including ‘modes of delivery for prehabilitation’ and ‘prehabilitation during neoadjuvant therapies’, aligned with current trends in cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Cost remains one of the major barriers for the adoption of new healthcare systems. This theme was considered important by experts, ‘cost effectiveness of prehabilitation programmes’, and while there are proposed models for evaluating the cost effectiveness of prehabilitation programmes, 20 , 21 current literature is lacking. Other priorities identified, including ‘modes of delivery for prehabilitation’ and ‘prehabilitation during neoadjuvant therapies’, aligned with current trends in cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In den letzten Jahren hat die Prähabilitation zunehmend an Bedeutung gewonnen [4,10]. Die Prähabilitation als präoperative Vorbereitung des Patienten ist weltweit -insbesondere in der onkologischen, koronarangiographischen und orthopädischen Chirurgie -bekannt, findet allerdings (noch) keine systematische Anwendung [11].…”
Section: Einleitung Zielsetzung Und Fragestellungunclassified
“…All deaths will be identi ed at the end of the trial by querying the regional death registries. QALY was chosen for the health economic evaluation because a German valuation set is available (37,45) and the use of the outcome type in the evaluation of prehabilitation is internationally recognised, as a recent systematic review has shown (20).…”
Section: Choice and Measurement Of Health Outcomesmentioning
confidence: 99%
“…Overall, the available body of evidence often focuses on cancer (10,12,16,14,17,18) or orthopaedic surgeries (11,19), and is predominantly of low quality. Moreover, recent systematic reviews did not identify any cost-effectiveness studies of prehabilitation in frail surgical patients of advanced age (20,15).…”
Section: Introductionmentioning
confidence: 99%